Comparative Investigation of the Reasons Propagating Maternal Mortality in Sweden, India and Rwanda - Puntambekar, Mehak; Lakkavally, Smitha; Bocchinfuso, Sara; Booher, Talia; Black, Ciara; Dennehy, Gina; Ryan, Alicia (Trinity Student Medical Journal, 2024)
Background: Haemorrhage, sepsis, and hypertensive disorders have been identified as the leading causes of maternal mortality worldwide. The majority of maternal deaths occur in developing countries and the majority are preventable. Despite the advent of technologies and scientific progress that have significantly reduced maternal mortality globally, developing countries disproportionately represent the majority of maternal deaths. Identifying and comparing countries with different maternal mortality rates is important because it provides an opportunity to reduce maternal death by understanding why and how we can learn from countries that perform well to inform and prioritize health policies, programmes and funding. Objectives: First, to identify the leading causes of maternal mortality in Sweden, India and Rwanda. Second, to identify the factors contributing to maternal death and the strategies used by said countries to address and/or decrease maternal mortality. Third, to identify strategies that could be adopted to reduce maternal death. Methods: International databases such as the World Health Organisation, World Bank, Population Reference Bureau, World Poverty Clock and the National Eclampsia Registry were used to identify key metrics. A scoping review was conducted in databases (PubMed Medline, Embase, Pubmed, Cochrane Library and Scopus) on quantitative and qualitative studies conducted in Sweden, Rwanda and India after 2000. We also searched for articles in search engines (Google Scholar and Google). Results: The research highlights that socioeconomic and demographic barriers contribute to the higher rates of maternal mortality seen in developing countries. The implementation of standardised guidelines for the use of drugs, investment in community-led care and the implementation of a midwifery model could play a key role in addressing maternal mortality in developing countries. Conclusion: It is understood that a multitude of factors contribute to maternal mortality. These perpetuating reasons are often closely interlinked in a complex relationship with the country's socioeconomic and political conditions. Therefore, in order to decrease maternal mortality rates in developing countries especially, the focus needs to be diverted towards bridging the gap between the urban and rural populations, and equipping mothers with accessible, affordable, and high-quality healthcare.